ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KESUKSESAN MERGER & AKUISISI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2005 – 2015 - Dewi Apriliani, Dewi Apriliani; Sigit Mulyanto, Sigit Mulyanto (Fakultas Ekonomi Universitas 45 Surabaya, 2020)
Several companies that carry out mergers & acquisitions can run successfully and not successfully. This study aims to find out what factors can effect the success of mergers and acquisitions, in this study using profitability ratios, leverage ratios, activity ratios, size and financial distress. The sampling method in this study are purposive sampling with a sample of 40 company that had a merger & acquisitions activities and were listed on Bursa Efek Indonesia from 2005 to 2015.The method of analysis in this study is by using logistic regression for predict the chances of success company to do merger & acquisitions and not success company to do merger & acquisitions. This study used significance level in 10%. The result showed that profitability ratio, leverage ratio, activity ratio, and financial distress did not have a significance effect on the success of company merger & acquisitions while size had a positive and significance effect on the success of company merger & acquisitions.